IMPACT OF RESONATING FREQUENCIES OF SOUND WAVES ON LOWER BACK PAIN RELATED TO VERTEBRAL MALALIGNMENT - Nimra Batool1, Mehrun Nisa1, Faheem Afzal2, Afzal Hussain3, Muhammad Saeed Ahmad4, Saima Batool1, Youssra Ashgar1, Asma Munir1 (Chelonian Research Foundation, 2024)
Lower back pain is a prevalent global health concern, with the incidence escalating due to an aging and expanding world population. This study aims to evaluate the efficacy of resonating sound waves in alleviating lower back pain associated with vertebral malalignment. A purposive non-probability sampling technique was employed to recruit participants aged 25 to 75 years, experiencing lower back pain linked to vertebral malalignment. The inclusion criteria encompassed mechanical etiologies, such as disc and nerve-related pain, while visible causes like infection, trauma, and tumors (organic causes) were excluded from the study. IBM SPSS and Microsoft Excel were utilized for data entry, graphing, and tabulation. The findings reveal a robust positive trend in reducing pain scores for patients undergoing pulsar treatment (P < 0.001). X-ray analyses demonstrated adjustments to disc spacing, facilitating vertebral realignment into a stable position. A comparison of pre- and post-treatment Numerical Pain Rating Scale (NPRS) scores revealed that resonating sound waves significantly improved pain relief in individuals suffering from chronic lower back pain. This study contributes to the growing body of evidence supporting the potential of resonating sound waves as an effective intervention for alleviating lower back pain associated with vertebral malalignment, thereby addressing a significant global health challenge. Keywords: Mechanical low back pain, Pulsar treatment, Resonating frequencies, Sound waves, Vertebral malalignment